Profiles of Disruptive Behavior Across Early Childhood: Contributions of Frustration Reactivity, Physiological Regulation, and Maternal Behavior - Calkins, Susan D. (Child development, 2008)
Disruptive behavior, including aggression, defiance, and temper tantrums, typically peaks in early toddlerhood and decreases by school entry; however, some children do not show this normative decline. The current study examined disruptive behavior in 318 boys and girls at 2, 4, and 5 years of age and frustration reactivity, physiological regulation, and maternal behavior in the laboratory at 2 years of age. A latent profile analysis resulted in 4 longitudinal profiles of disruptive behavior, which were differentiated by interactions between reactivity, regulation, and maternal behavior. A high profile was associated with high reactivity combined with high maternal control or low regulation combined with low maternal control. Results are discussed from a developmental psychopathology perspective